АРАБ ӘРІПТЕРІНІҢ МИСТИКАЛЫҚ СИМВОЛИКАСЫ ЖӘНЕ СОПЫЛАР МЕН АЛХИМИКТЕРДІҢ ҚҰПИЯ ТІЛДЕРІ - Сейтхан, А. Н. (Journal of Oriental Studies, 2016)
The semantic meaning of Arabic letters has began to develop “Arabic calipa cali-phate” Later, this doctrine has become has turned to the whole current under the name "Hurufizm" in some countries of the Central Asia. Also, were well-known “Sufiis”, who have developed this technique of encoding letters letters for an exchange among them-selves secret information to the most unique heights.